Promoting Women's Inclusion in Latin American Technology: A Multineutrosophic Analysis for Strategic Decision-Making - Giannina Marleni Castillo Castillo; Giannina Marleni Castillo Castillo; Stefanny Fiorella Bazán-Arias; Katherine Lizzeth Vallejos-Tantajulca; Kiara Melanie Chauca-Justiniani; Rosa María Criollo Delgado (Neutrosophic Sets and Systems)
This study addresses the underrepresentation and persistent gender inequalities hindering women's inclusion in Latin America's technology sector. Utilizing a systematic literature review of 58 articles (2015-2022) and a multineutrosophic analysis approach employing the ARAS method, the research aims to identify and prioritize strategic guidelines for promoting female participation while accounting for inherent uncertainty and multiple perspectives. The methodology integrates diverse expert opinions to provide a robust framework for decision-making. Findings indicate that promoting technological education and strengthening inclusive policies are the most impactful strategies, significantly influencing equity, sustainability, and accessibility. Support for female entrepreneurship and leadership development also emerged as important, albeit secondary, priorities. This research contributes a novel application of multineutrosophic analysis to a critical social challenge, offering a systematic method for evaluating complex strategies and providing actionable recommendations to accelerate women's inclusion and foster regional technological and social development.